Elite Persistence and Policy Persistence: Re-Installed Mayors from Weimar Germany - Remo Nitschke; Felix Roesel (Center for Economic Studies and ifo Institute (CESifo), 2023)
Why do public policies change little over time in individual places, sometimes for centuries? We investigate different mechanisms for policy persistence. Several city mayors serving in democratic Weimar Germany were expelled by the Nazis in 1933, but re-installed by the Allies after World War II. We find that pre-Nazi patterns in public debt re-appear in cities with a re-installed mayor, albeit all city debt defaulted after the war. We do not find such correlations in a matched sample of cities where the Weimar mayor did not return to office. Historical public debt does also not predict debt today in East Germany and in former German cities in present-day Poland–places where political elites or most of the population changed. We conclude that elite persistence dominates place-based features such as geography or population preferences in explaining persistent policies.
Keywords: H63; H74; N44; N94; 330; elite persistence; public debt; fiscal policy; Weimar Germany